The Internationalization of Judicial Review in the Colombian High Courts - Juan Sebastián Villamil Rodriguez (Constitutional Review, 2019)
The internationalization of adjudication in the Colombian high court refers to the growing importance that the American Convention on Human Rights has gained among the judicial forums of this country, but especially to the phenomenon that occurs when national judiciaries implement and appropriate the doctrine of the control of conventionality. The Convention has claimed a high ground in the Colombian constitutional system due to the appropriation of international law by national courts decisions, and to the process of the internationalization of the law. By consistently applying the control of conventionality doctrine, courts like the State Council have reaffirmed the binding nature and the effectiveness of the decisions of the Inter-American Court of Human Rights for the Colombian legal system. In contrast to a much more regressive posture assumed by the Constitutional Court in recent decisions, the State Council, drawing on the legal contents of international law, has broadened the range of legal sources for rights interpretation in Colombia. By this action, as it will be further stated in this article, the State Council has contributed to a move away from a paradigm of a legalism based solely on the state sovereignty and national constitutionalism, towards one that endorses the pluralist structure of post-national law. Against this background, this article aims to discuss how the relationship of national judiciaries with international law is best understood as reflecting the development of a pluralist legal dynamic, sometimes referred to as jurisprudential dialogue, that involves the broadening of the normative horizon and the internationalization of the sources available for national judges in their reasoning; particularly in the cases that involve human rights violations.